Deep-learning model for embryo selection using time-lapse imaging of matched high-quality embryos - Lisa Boucret; Floris Chabrun; Magalie Boguenet; Pascal Reynier; Pierre-Emmanuel Bouet; Pascale May-Panloup (Scientific Reports)
Abstract Time-lapse imaging and deep-learning algorithms are promising tools to assess the most viable embryos and improve embryo selection in IVF laboratories. Here, we developed and validated a deep learning model based on self-supervised contrastive learning. The model was developed with a new approach based on matched KID (Known Implantation Data) embryos derived from the same cohort of a stimulation cycle, both judged to be of good quality according to classical morphological criteria and morphokinetics, transferred fresh or frozen, but with a different implantation fate (clinical pregnancy vs. failure of implantation). We used self-supervised contrastive learning to train convolutional neural networks to ensure an unbiased and comprehensive learning of the morphokinetics features of the embryos, followed by a Siamese neural network fine-tuning and an XGBoost final prediction model to prevent overfitting. 1580 embryo videos of 460 patients were included between January 2020 and February 2023. With the knowledge of the implantation outcome of a previous transfer of an embryo derived from the same stimulation cycle, this model could predict the pregnancy outcome of the subsequent transfer with an AUC of 0.57. Without any knowledge of transfer history, the model achieved a satisfactory performance in predicting implantation (AUC = 0.64). This model could be considered as an adjunct tool for biologists to better select embryos and reduce the number of useless transfers per patient, when a cohort with several embryos classified as good quality by classical criteria is obtained.